Spatial Variation of Leaf Chlorophyll in Northern Hemisphere Grasslands - Zhang, Yao; Li, Ying; Wang, Ruomeng; Xu, Li; Li, Mingxu; Liu, Zhaogang; Wu, Zhenliang; Zhang, Jiahui; Yu, Guirui; He, Nianpeng (Frontiers in Plant Science, 2020)
Chlorophyll is the molecular basis for the function of photosystems and is also a promising tool for ecological prediction. However, the large-scale patterns of chlorophyll variation in grasslands remain poorly understood. We performed consistent measurements of chlorophyll a, b, a+b, and the a:b ratio (chlorophyll a/b) for 421 species across northern hemisphere grassland transects, recorded their distributions, variations, and influencing factors, and examined their relationships with leaf nitrogen. The results showed that the distributional ranges were 0.52–28.33 (mean 5.49) mg•g−1 dry weight, 0.15–12.11 (mean 1.83) mg•g−1 dry weight, 0.67–39.29 (mean 7.32) mg•g−1 dry weight, and 1.28–7.84 (mean 3.02) for chlorophyll a, b, a+b, and a/b, respectively. The chlorophyll averages differed among regions (higher in the Loess Plateau and the Mongolian Plateau than in the Tibetan Plateau), grassland types (desert grasslands > meadow > typical grasslands), life forms, life spans, and taxonomies. In the entire northern hemisphere grassland, chlorophyll concentrations and chlorophyll a/b were negatively correlated to photosynthetically active radiation and the soil N:P ratio, and positively correlated to the mean annual temperatures. These results implied that chlorophyll in grasslands was shaped by the layered structure of grasses, distinct plateau environments, and phylogeny. The allocation patterns of leaf nitrogen to chlorophyll differed among regions and grassland types, showing that caution is required if simply relating single leaf N or chlorophyll to productivity separately. These findings enhance our understanding of chlorophyll in natural grasslands on a large scale, as well as providing information for ecological predictive models.